Mapa Teatro, Mockus, and Modos de hacer - Wilson, Geoffrey (Latin American Theatre Review, 2016)
This article analyzes the relationship between cultura ciudadana —the social-engagement program of Colombian sociologist and former mayor of Bogotá Antanas Mockus— and the artistic practice of Bogotá’s Mapa Teatro, particularly those works that focus on the demolished barrio known as El Cartucho. Particular attention is paid to how the politician and the artists share an understanding of citizenship/belonging that emphasizes the repertoires of behavior embedded in shared social space. The analysis of these behavioral histories builds on the valuable work of those who have written on Mapa Teatro, such as Ileana Diéguez, Karen Till, Doreen Massey, and Vicky Unruh, while shedding new light on how Mapa Teatro’s dramaturgy engaged with Mockus’ cultural politics to challenge the stigmatization and marginalization of a community through an emphasis on the relationship between histories of behavior in social space and the construction of cultural citizenship.